Peran Program Pertukaran Pelajar MBKM dalam Pengembangan Kompetensi Lulusan - Suleha Ecca; Ahmad Mustanir; Jamaluddin Ahmad; Pratiwi Ramlan; Khaeriyah Adri; Mardhatillah Mardhatillah; Zulkarnain Sulaiman (Universitas Indraprasta PGRI Jakarta, 2022)
This research aims at finding out the role of one of the MBKM programs, namely Student Exchange in the development of competencies / skills of graduates of Muhammadiyah Sidenreng Rappang University. The MBKM program was born so that universities no longer put together, equalize and integrate between the fields of education and job training and work experience, but more broadly towards real experiences for students. This real experience will certainly enhance the competence / skills of students so that they will become graduates who earn a decent income according to the first point of Main Performance Indicators. This research is carried out in 2021 using quantitative methods. The subjects of this study were all students (population survey). Data is collected through the SPADA Dikti Survey and analyzed with frequency tabulation. Research results as many as 60% of students choose the Student Exchange program, as many as 60% of students stated that there was an increase in soft skills well after participating in MBKM activities, as many as 74% of students stated MBKM activities for universities according to the needs of graduates in the future, 91% of students expressed interest in the MBKM program.